2023
DOI: 10.21203/rs.3.rs-3324840/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of clinical features, prognosis and potential target genes of refractory meningioma-- Research based on multiple databases

Shiwei Li,
Mengjiao Li,
Kaitao Zhu
et al.

Abstract: Objective: Analyzing SEER database data on malignant meningiomas, we explored high-risk factors for refractory meningiomas (RMs). Additionally, we analyzed GEO database genes across WHO grades to identify key genes and malignant risk factors for RMs. Immunohistochemical analysis was performed on WHO grade meningiomas' pathological specimens to verify hub gene expression differences. Methods: We included clinical cases of malignant meningiomas diagnosed in the SEER database. GEO database provided a gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A recent study has reported that the expression of EGFR was observed to be more prevalent in meningioma of grade II and III as compared to those of grade I. 23 The research additionally discovered that the expression of EGFR was correlated with an increased likelihood of tumor recurrence and mortality.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent study has reported that the expression of EGFR was observed to be more prevalent in meningioma of grade II and III as compared to those of grade I. 23 The research additionally discovered that the expression of EGFR was correlated with an increased likelihood of tumor recurrence and mortality.…”
Section: Discussionmentioning
confidence: 97%
“…16 Ciardiello et al, conducted a recent study that revealed that the expression of EGFR was linked to heightened tumor growth and invasion in cell lines of meningioma. 22,23 Ciardiello and colleagues have reported that the use of EGFR inhibitors can effectively target the overexpression of EGFR, resulting in a reduction in tumor growth and invasion in cell lines. 22 We did not find any significant correlation between the intensity of EGFR-1 expression and the grade of meningioma in Grade II meningioma cases (p=0.248).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations